Molecular background of the diverse metabolic profiles in leaves and inflorescences of naked catmint (Nepeta nuda L.) - Petrović, Luka; Filipović, Biljana; Skorić, Marijana; Šiler, Branislav; Banjanac, Tijana; Matekalo, Dragana; Nestorović Živković, Jasmina; Dmitrović, Slavica; Aničić, Neda; Milutinović, Milica; Božunović, Jelena; Gašić, Uroš; et al. (Frontiers in Plant Science, 2024)
Nepeta nuda L. shares a typical secondary chemistry with other Nepeta species (fam. Lamiaceae), characterized by the tendency to intensively produce monoterpenoid iridoids, whereas the phenylpropanoid chemistry is steered towards the production of a caffeic acid ester, rosmarinic acid. Combining complementary state-of-the-art analytical techniques, N. nuda metabolome was here comprehensively characterized in the quest for the organ-specific composition of phenolics and terpenoids that possess well-defined functions in plant-biotic interactions as well as therapeutic potential. N. nuda inflorescences showed generally higher constitutive levels of specialized metabolites, as compared to leaves, and the composition of major iridoids and phenolics in reproductive organs was found to be more conserved than in leaves across 13 populations from the Central Balkans. The results suggest that N. nuda plants most likely invest more in constitutive than inducible biosynthesis of functional metabolites in flowers, since they are of essential importance for both pollination and defense against herbivores and pathogens. Conversely, specialized metabolism of leaves is found to be more susceptible to reprograming in response to differential growth conditions. The defense strategy of leaves, primarily functioning in CO2 fixation during photosynthesis, more likely relies on the induction of metabolite levels following plant-environment interplay. Organ-specific biosynthesis of iridoids in N. nuda is found to be tightly regulated at the transcriptional level, and high constitutive levels of these compounds in inflorescences most likely result from the up-regulated expression of several key genes (NnG8H, NnNEPS1, NnNEPS2, and NnNEPS3) determining the metabolic flux through the pathway. The organ-specific content of rosmarinic acid and co-expression patterns of the corresponding biosynthetic genes were much less correlated, which suggests independent organ-specific transcriptional regulation of the iridoid and phenolic pathways. Knowledge gathered within the present study can assist growers to select productive genotypes and manipulate phenology of N. nuda towards maximizing yields and facilitating its integration into pest management systems and other applications related to human health.